AGRONOMIC PERFORMANCE OF SINGLE HEAD BROCCOLI CULTIVARS UNDER PROTECTED ENVIRONMENT IN TROPICAL CONDITIONS - Antunes, Darley Tiago; Seabra Júnior, Santino; Zanuzo, Marcio; Ponce, Franciely Da Silva; Neves, Jucimar Ferreira; Trento, Daiane Andréia; Dallacort, Rivanildo (REVISTA DE AGRICULTURA, 2018)
Growing broccoli in tropical regions is a challenge, as high temperatures hamper plant development. The objective of this work was to evaluate broccoli cultivars of the single inflorescence type under protected environment under tropical conditions. The cultivation was carried out in a protected arc-type environment, covered with a 120μm anti-UV-A and UV-B plastic film. A randomized block design (DBC) with four cultivars (BRO068, Imperial, Salinas and TPC07118) was used, with six replications. It was evaluated: Fresh weight (g plant-¹), curd diameter (cm), Yeld (ton ha-¹). plant height (cm), cycle, inflorescence emission, the harvest period and adaptability. The visual aspect index and the commercial classification were also evaluated. The "Imperial" hybrid presented better adaptation to the crop and higher productivity with 7.69 t ha-1.